2021
DOI: 10.1002/jum.15897
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Pressure Estimation for Diagnosing Portal Hypertension in Patients Undergoing Dialysis for Chronic Kidney Disease

Abstract: Objectives-Hepatic venous pressure gradient (HVPG) is considered the standard in quantifying portal hypertension, but can be unreliable in dialysis patients. A noninvasive ultrasound technique, subharmonic-aided pressure estimation (SHAPE), may be a valuable surrogate of these pressure estimates. This study compared SHAPE and HVPG with pathology findings for fibrosis in dialysis patients.Methods-This was a subgroup study from an IRB-approved trial that included 20 patients on dialysis undergoing SHAPE examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
(245 reference statements)
0
6
1
Order By: Relevance
“…First, optimization of parameters to improve the correlation coefficient. A trial 5 in 20 patients undergoing dialysis for chronic kidney disease showed a moderate correlation between SHAPE and HVPG ( r = 0.45), which is lower than the previous one. The cause of the variable and unsatisfied correlation coefficient needed to be solved.…”
Section: Figurecontrasting
confidence: 64%
See 2 more Smart Citations
“…First, optimization of parameters to improve the correlation coefficient. A trial 5 in 20 patients undergoing dialysis for chronic kidney disease showed a moderate correlation between SHAPE and HVPG ( r = 0.45), which is lower than the previous one. The cause of the variable and unsatisfied correlation coefficient needed to be solved.…”
Section: Figurecontrasting
confidence: 64%
“…Monodisperse microbubbles specifically designed for SHAPE using a commercially available microfluidics device (Solstice Pharmaceuticals) have the potential to greatly increase sensitivity to hydrostatic pressure compared to relying on polydisperse agents designed for diagnostic imaging. In addition, the variable correlation coefficient between SHAPE and liver fibrosis is presented in PH patients with other comorbidity (e.g., chronic kidney disease) 5 . Further large‐scale prospective studies are needed to perform to evaluate the clinical application of SHAPE.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Evaluate vasculature and portal pressures. [1][2][3][4][5][6] a. Determine hepatic artery, portal vein, and hepatic vein patency.…”
Section: Detect Arterial Phase Hyperenhancement Whenmentioning
confidence: 99%
“…According to the data using SHAPE to differentiate between mild (stage 0–1) and moderate to severe (stage 2–4) fibrosis in patients with dialysis, SHAPE succeeded (-10.4 ± 4.9 dB vs.−5.4 ± 3.2 dB; P = 0.035), but HVPG failed (3.0 ± 0.6 mmHg vs. 4.8 ± 0.7 mmHg; P = 0.30) ( 25 ). The diagnostic accuracy by SHAPE was 80%, whereas that by HVPG was 76%.…”
Section: Us Based On Circulating Microbubblesmentioning
confidence: 99%